Implementation in nursing and midwifery. A scoping review / Implementationsprojekte in der Pflege und Hebammenarbeit. Scoping review - Loytved Christine Anna Lieselotte; Hasenberg Gabriele; Brendel Karin; Bothe-Moser Cornelia; Eggenschwiler Ruth; Eigenmann Denise; Graf Petra; Hammer Kristin; Hauser Regula; Oberndörfer Katrin; Pfister-Stoppa Anja; Spiegel-Hefel Elisabeth; et al. (Sciendo, 2017)
Evidence-based expertise in nursing and midwifery is growing but is not automatically turned into practice. The importance of implementation research is therefore increasing. International research results on factors facilitating implementation have not yet been sufficiently presented.